1994
DOI: 10.1016/0735-1097(94)90141-4
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-dependent dilation in the systemic arteries of asymptomatic subjects relates to coronary risk factors and their interaction

Abstract: Loss of endothelium-dependent dilation in the systemic arteries occurs in the preclinical phase of vascular disease and is associated with interaction of the same risk factors known to predispose to atherosclerosis and its complications in later life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
672
8
44

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,132 publications
(760 citation statements)
references
References 28 publications
36
672
8
44
Order By: Relevance
“…Sample size calculations were performed based on the FMD component of the study. In previous studies of healthy subjects, reported mean FMD values have ranged from 106% to 112% (SD 3-6.5%), while in subjects with vascular risk factors such as cigarette smoking, hypertension, or hypercholesterolemia, mean FMD ranged from 100% to 106.5% (20,36,37). For the purpose of sample size calculations we estimated a mean Ϯ SD FMD of 108 Ϯ 4% in our healthy controls.…”
Section: Methodsmentioning
confidence: 99%
“…Sample size calculations were performed based on the FMD component of the study. In previous studies of healthy subjects, reported mean FMD values have ranged from 106% to 112% (SD 3-6.5%), while in subjects with vascular risk factors such as cigarette smoking, hypertension, or hypercholesterolemia, mean FMD ranged from 100% to 106.5% (20,36,37). For the purpose of sample size calculations we estimated a mean Ϯ SD FMD of 108 Ϯ 4% in our healthy controls.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 These findings suggested that endothelial dysfunction contributes significantly to CAD progression and cardiovascular event rates. 14,15 Numerous studies have confirmed the independent prognostic relevance of hsCRP for the risk of cardiovascular events in patients with stable or unstable CAD and also in apparently healthy subjects. 6,7,16 Fichtlscherer et al indicated that elevated serum CRP levels indicative of a systemic inflammatory response reflected a blunted systemic endothelial function, and normalization of CRP levels over time was associated with a significant improvement in endothelium-mediated blood flow responses.…”
Section: Endothelial Function Inflammatory Marker Of Hscrp and Athementioning
confidence: 96%
“…In addition, oxygen free radicals impair endothelial function through direct inactivation of NO (84). While all traditional risk factors have been associated with peripheral endothelial dysfunction, a close quantitative relationship does not exist (85)(86)(87)(88). This suggests that endothelial function measurements may add unique information not captured by Framingham risk scores.…”
Section: Relationship Of Endothelial Function To Risk Factors and Thementioning
confidence: 99%